1980
DOI: 10.1073/pnas.77.12.7232
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-orientation of lecithin crystals.

Abstract: For the purpose of clarifying the magnetoorientation mechanism of several biological membrane systems, xylene-suspended thin-layered single crystals of lecithin, which is a major component of membranes, were subjected to magnetic fields of various strengths, and the orientation behavior of the crystals was analyzed. Lecithin crystals oriented in such a way that the directions of both the hydrocarbon chains and the phosphorylcholine group of the lecithin molecule were perpendicular to the magnetic field, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…If ⌬ Ͻ 0, there is an energetically favorable orientation of the molecules perpendicular to the direction of B 0 , and this is the case for phospholipids and egg lecithins (48,49,51). Values of Ϫ0.28 ϫ 10…”
Section: Orientation and Viscositymentioning
confidence: 96%
See 1 more Smart Citation
“…If ⌬ Ͻ 0, there is an energetically favorable orientation of the molecules perpendicular to the direction of B 0 , and this is the case for phospholipids and egg lecithins (48,49,51). Values of Ϫ0.28 ϫ 10…”
Section: Orientation and Viscositymentioning
confidence: 96%
“…The orientation of bicelles in a magnetic field is explained by the anisotropy of the magnetic susceptibility tensor, , of the phospholipids acyl chains (48,49) and, to a lesser extent, the contribution of the ester groups (48,50). The anisotropy of the magnetic susceptibility is the difference between the magnetic susceptibilities parallel ( ) and perpendicular ( Ќ ) to the axis of a molecule:…”
Section: Orientation and Viscositymentioning
confidence: 99%
“…Generally, these polymers display a higher degree of order in a strong magnetic field than they do in the geomagnetic field, a finding that is again based on the diamagnetism of the polymers, and that constitutes a great boon to structural studies. A nice example is the magneto-orientation of lecithin crystals, which orient in such a way that the hydrocarbon chain and phosphorylcholine group directions, which are orthogonal to each other, are perpendicular to the field direction (Sakurai et al 1980). Knowledge about lecithin is particularly relevant, because it constitutes an important membrane compound, and because membranes from various sources, such as retinal rod-outer segments, chloroplasts and purple membranes from Halobacterium halobium, orient in magnetic fields.…”
Section: Biopolymersmentioning
confidence: 98%
“…Since this part of the myelin sheath is hardly accessible by water, approximation of the water environment by cylindrical spaces appears appropriate. However, it has been suggested that some of the anisotropy may arise from phospholipid headgroups (17), which are hydrophilic and more readily accessible by water. For example, the molar anisotropy associated of carboxyl, which is part of the headgroup (See Figure), is about a quarter of that of the lipid acyl chain (16).…”
mentioning
confidence: 99%